2022
DOI: 10.4103/2045-9912.330693
|View full text |Cite
|
Sign up to set email alerts
|

Color change after tooth bleaching with ozone and 10% ozonized carbamide peroxide for in-office use

Abstract: There is a constant search for bleaching treatments that can offer greater safety with fewer adverse effects, especially in the techniques performed in the office, which usually employ hydrogen peroxide in high concentrations (35% to 40%) that are not recommended by some international control agencies. This in vitro study evaluated the color change after tooth bleaching with the use of ozone and a 10% ozonized carbamide peroxide bleaching treatment for in-office use. Thirty molars were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The bleaching protocols evaluated are shown in Table 1 . The ozone concentration in the ozone gas therapy followed protocols adapted from Tessier et al 25 , Santana et al 18 , and Ferreira et al 19 . The pH values for the 10% carbamide peroxide bleaching agent and the ozonized 10% carbamide peroxide were measured in triplicate, at different application times (baseline, 30, and 60 minutes), using a pH meter (MS Tecnopon Equipamentos Especiais, Piracicaba, SP, Brazil).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The bleaching protocols evaluated are shown in Table 1 . The ozone concentration in the ozone gas therapy followed protocols adapted from Tessier et al 25 , Santana et al 18 , and Ferreira et al 19 . The pH values for the 10% carbamide peroxide bleaching agent and the ozonized 10% carbamide peroxide were measured in triplicate, at different application times (baseline, 30, and 60 minutes), using a pH meter (MS Tecnopon Equipamentos Especiais, Piracicaba, SP, Brazil).…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies have observed that the isolated use of ozone did not promote effective bleaching 16,20,24 , others have reported that ozone associated with a high concentration of hydrogen peroxide (37.5% 18 and 38% 13-15 ) during in-office bleaching techniques did so. Ozone applied together with carbamide peroxide in the office 19 or by patients on their own 18,19,25 has shown significant results in inducing clinically noticeable color change, in addition to reducing patient-reported sensitivity 14 . These differences in the whitening potential reported for ozone therapy in different studies stem from variations in ozone or peroxide dosages or low concentrations, low sample size, older ozone generation devices, and ozone circulation capacity in the application tray 15 , 19 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations